The Rise in Executive Compensation - Consequence of a 'War for Talents'? - Katja Rost (Center for Research in Economics, Management and the Arts (CREMA), 2010)
The rise in executive compensation has triggered a great amount of public controversy and academic research. Critics have referred to the salaries paid to managers as 'pay without performance', while defenders have countered that the large salaries can be explained by a 'war for talents'. This research tests whether a war for talent provides an explanation. The rise in executive compensation in recent years is explained by the assumption that, over the past decades, general managerial skills have become more important relative to firm-specific knowledge for the production of managers. A shift toward transferable managerial skills requires higher compensation, particularly in large firms, to attract and retain managerial talents. Relying on an internationalized and deregulated managerial labor market, i.e. the Swiss banking sector, the empirical findings confirm that a shift toward transferable managerial skills in large firms is indeed an explanation for the rise in executive compensation. However, the shift towards transferable managerial skills in large firms does not improve firm performance, giving no supporting evidence for a war for talent. It is discussed how transferable managerial skills may used to legitimize higher compensation at the top, e.g. by promulgating definitions of talent in elite labour markets.
Keywords: 330; Executive compensation; efficient labor market view; transferable skills; outside options